Face detection with multiple cameras - Kho, Anthony. (2009)
This work developed a framework for face detection in a dual-camera surveillance system consisting of an omnidirectional camera and four Pan-Tilt-Zoom (PTZ) cameras. The omnidirectional camera that provides a wide angle 360 degree field-of-view is used to detect a face. Next, the PTZ cameras that provide high resolution images will focus on the detected face such that the frontal area of the face can always be captured.